EXCURSION AS AN EFFECTIVE MODEL FOR INTERRELIGIOUS LITERACY TO PROMOTE MODERATE CULTURE IN PLURAL SOCIETY - Subagya, Agus (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2023)
Moderation is more than a simple concept; it is also a way of life. In order to make moderation a daily practice, enormous efforts must be made during the process of socialization and until it becomes a movement. This study aims to describe and analyse the strategies and actions of interfaith young people in Jembrana, Bali, who promote the value of moderate culture. Using a qualitative approach through participant observation model within the framework of social construction, this study found that the excursion to the interfaith communities and religious worship houses became an effective medium for increasing moderate culture awareness and practice. The trip, as a genuine activity of young people, is the result of mapping the issues and potential actors involved in the movement by considering the network for disseminating the values of moderation. The actions initiated by the students of MAN 1 Jembrana, which then involved interfaith young people from various schools in Jembrana, started with a weekly routine discussion related to diversity issues, then continued with visits and social services to various places of worship as well as religious institutions. After all, the action ended with a declaration of fraternity and an interfaith commitment to peacekeeping